Tingkat Kecerdasan Anak dalam Perspektif Spiritualitas Islam: Sebuah Tinjauan Kepustakaan - Abid, Ahsanul (Global Action and Education for Society, 2025)
This study examines the dominance of cognitive approaches in early primary education (grades 1–3), which often neglect essential dimensions such as emotional, social, moral, and spiritual development. Using a literature review method, this research explores child development theories (Piaget, Erikson, Vygotsky), multiple intelligences (Gardner), emotional intelligence (Goleman), and Islamic psychological perspectives from the thoughts of Al-Ghazali and Al-Attas. The findings indicate that an education system overly focused on academic achievement fails to accommodate children’s diverse potentials. Islamic education emphasizes a balance between intellect (‘aql), heart (qalb), and actions (‘amal). Therefore, a holistic, contextual, and spiritually grounded approach to early education is necessary. This study recommends curriculum reorientation, authentic assessment, teacher training, and parental involvement as key foundations for balanced child development and character formation.